Profitabilitas, Kebijakan Dividen, Struktur Modal dan Likuiditas terhadap Harga Saham - Dinda Widyaningrum; G. Anggana Lisiantara (Journal of Management and Bussines (JOMB), 2022)
This study aims to re-examine the effect of profitability, dividend policy, capital structure and liquidity on stock prices. This research method is quantitative. The research source used is secondary data. The method used is multiple linear regression equation. The population and samples were taken from manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The results showed that the ROA variable had an effect on stock prices, with a significant value of 0.000 <0.05 and a t-value of 5.130 > 1.99495; b) the DPR, LTDER and CR variables do not have a significant effect on stock prices, because they have a significant value of more than > 0.05 and t count > t table 1.99495. In conclusion, profitability (ROA) has a significant influence on stock prices. Meanwhile, dividend policy (DPR), capital structure (LTDER) and liquidity (CR) have no effect on stock prices. Keywords: Stock Price, Dividend Policy, Liquidity, Profitability, Capital Structure